The politics of poverty reduction - Mosley, Paul. (Oxford : Oxford University Press, 2012)
Poor people everywhere are politically weak, and yet poverty in some developing countries has gone down dramatically. Why is this? Using nine country case-studies this book provides answers by examining government alliances, the role of aid donors and NGOs, and policies on labour, tax and expenditure.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Poverty -- Political aspects; Poverty -- Case studies